Effects of Antioxidant Intake on Fetal Development and Maternal/Neonatal Health during Pregnancy - Giorgia Sebastiani; Elisabet Navarro-Tapia; Laura Almeida-Toledano; Mariona Serra-Delgado; Anna Lucia Paltrinieri; Óscar García-Algar; Vicente Andreu-Fernández (MDPI AG, 2022)
During pregnancy, cycles of hypoxia and oxidative stress play a key role in the proper development of the fetus. Hypoxia during the first weeks is crucial for placental development, while the increase in oxygen due to the influx of maternal blood stimulates endothelial growth and angiogenesis. However, an imbalance in the number of oxidative molecules due to endogenous or exogenous factors can overwhelm defense systems and lead to excessive production of reactive oxygen species (ROS). Many pregnancy complications, generated by systemic inflammation and placental vasoconstriction, such as preeclampsia (PE), fetal growth restriction (FGR) and preterm birth (PTB), are related to this increase of ROS. Antioxidants may be a promising tool in this population. However, clinical evidence on their use, especially those of natural origin, is scarce and controversial. Following PRISMA methodology, the current review addresses the use of natural antioxidants, such as epigallocatechin gallate (EGCG), melatonin and resveratrol (RESV), as well as other classical antioxidants (vitamin C and E) during the prenatal period as treatment of the above-mentioned complications. We review the effect of antioxidant supplementation on breast milk in lactating mothers.